2020
DOI: 10.20944/preprints202003.0364.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effects of Outdoor Air Pollution Concentrations and Lockdowns on Covid-19 Infections in Wuhan and Other Provincial Capitals in China

Abstract: Background: Covid-19 was first reported in Wuhan, China in Dec 2019. Since then, it has been transmitted rapidly in China and the rest of the world. While Covid-19 transmission rate has been declining in China, it is increasing exponentially in Europe and America. Although there are numerous studies examining Covid-19 infection, including an archived paper looking into the meteorological effect, the role of outdoor air pollution has yet to be explored rigorously. It has been shown that air pollution will weake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…Nevertheless, because these models 'scale up' observed deaths to estimate population infections, small differences in the assumed case fatality will have substantial effects on the results. This poses a challenge for estimation, given that there is considerable uncertainty regarding the case fatality rate, which may vary widely across regions due to local demographics and environmental conditions [27][28][29][30][31]. Moreover, to the extent that there is significant undercounting in the number of COVID-19 related deaths [32,33], these estimates may fail to capture the full extent of population infection.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, because these models 'scale up' observed deaths to estimate population infections, small differences in the assumed case fatality will have substantial effects on the results. This poses a challenge for estimation, given that there is considerable uncertainty regarding the case fatality rate, which may vary widely across regions due to local demographics and environmental conditions [27][28][29][30][31]. Moreover, to the extent that there is significant undercounting in the number of COVID-19 related deaths [32,33], these estimates may fail to capture the full extent of population infection.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, because these models 'scale up' observed deaths to estimate population infections, small differences in the assumed case fatality will have substantial effects on the results. This poses a challenge for estimation, given that there is considerable uncertainty regarding the case fatality rate, which may vary widely across regions due to local demographics and environmental conditions [27][28][29][30][31]. Moreover, to the extent that there is significant undercounting in the number of COVID-19 related deaths [32,33], these estimates may fail to capture the full extent of population infection.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental quality index serves as a comprehensive indicator to analyze the impact of environmental quality on human health. Based on Chinese provincial dataset from December 01, 2019, to March 20, 2020, Han et al (2020) concluded that lower environmental quality is negatively correlated with human immune system and as a consequence, it is contributing towards COVID-19 pandemic in countries with poor environmental quality. Similarly, Venter et al (2020) reinforced comparable discoveries and recommended that better environmental quality lowers the risk of getting infected from COVID-19.…”
Section: Methodsmentioning
confidence: 99%